“A parte mais odiosa é obedecer!”: as relações de poder e as práticas de liberdade das crianças pequenas na educação infantil - Costa, Rebeka Rodrigues Alves da (2022)
The main objective of this research was to investigate what is revealed through power relations and the possible practices of freedom of children from a Pre-School class, in the context of the attendance of Early Childhood Education caused by the Covid-19 pandemic. It was intended to i) discover the social interactions of children in kindergarten class, in the context of Early Childhood Education care caused by the Covid-19 pandemic; ii) describe how power relations are revealed in this context, and iii) identify possible practices of freedom in the children's relationships that point to the ways they have to resist power relations. The theoretical body of this work was based on the studies of the philosopher Michel Foucault (1979; 1995; 1999; 2006a; 2006b; 2008, 2013) to understand power, power relations and the practices of freedom; in authors who have developed research in the field of Childhood Studies (ARIÉS, 1981; SARMENTO, 2007; CORSARO, 2002; CORSARO, 2011; FERREIRA, 2004a; FERREIRA, 2004b; HEYWOOD, 2004) to support an understanding of the concepts of child and childhood and in the Philosophy of Education (KOHAN, 2003; 2007; 2019; 2021; LARROSA, 2011; 2017a; 2017b; 2018) to build a reflection on childhood time and school as a scholé. The investigative work had its methodology based on the principles of the Qualitative Approach (MINAYO, 2009; BOGDAN; BIKLEN, 1994) and set up as a field survey with ethnographic inspirations (ANDRÉ, 1995). The methodological procedures used to generate the data were the participative observation (MINAYO, 2009; ANDRÉ, 1995), interview conversations (SARAMAGO, 2001), and Completion Stories, by Madeleine B. Thomas (CRUZ, 2006). The actors and the locus of the research were 14 children from a kindergarten class 5 from a private school located in Fortaleza-CE. The reflection based on the data showed that the children's interactions are crossed by power relations and they both suffer the effects of power and exercise it in their relationships with others. In the relationships between adults and children, power is materialized in the control of the bodies and conduct of children's behavior. Playing and subtle verbal threats sometimes are used as a technology of power and a bargaining currency at school. In peer relationships, disputes were found related to gender, and confrontations between children of the same gender have been observed, so that power is exercised in these relationships in the form of screams, beating gestures, impositions of wills, and verbal and corporal threats. In turn, children exercise freedom and express resistance to power. Reflecting on these points of confrontation revealed that children ask adults to learn from them and their ways of living childhood. They argue that a teacher provides good government for all, as long as he/she remains inventive, values play time, listens to what each child has to say, allows time for boys and girls to be with themselves and with others, promotes experiences, doesn't impose that everyone has to do the same thing at the same time and provide moments with nature and outdoors. In this sense, what they seem to demand is an Early Childhood Education that is built based on childhood experience.